THE ROLE OF INSTRUCTIONAL LEADERSHIP IN THE IMPLEMENTATION OF INDEPENDENT CURRICULUM AT SMAN GERUNG - Mustari, Mohamad; Fauzan, Ahmad; Kurniawansyah, Edy (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education is a deliberate and planned effort to create a teaching and learning environment where students can actively develop their potential to have personality, character, a sense of self-control, religious spiritual soul, and knowledge to live a life in society. Education is changing in the home, community, and educational institutions. The instructional leadership role of school principals as educators, managers, administrators, leaders, innovators and motivators cannot be separated from educational change in schools. One of the three implementers of the Driving School Program (PSP) is SMA Negeri 1 Gerung. Where PSP is a government program that collaborates with regional governments (PEMDA) in various interventions to improve the level of education. PSP concentrates on the process of developing holistic student learning outcomes which include basic literacy and numeracy competencies as well as character. The research approach used is empirical research, namely research with data in the field as the main data source, such as the results of interviews and observations. In this research, the researcher focuses on SMAN 1 Gerung which is the implementer of the Driving School Program (PSP) in Lombok Regency West.